Pengaruh Pengajaran Keuangan Orang Tua terhadap Perilaku Keuangan yang Dimediasi oleh Sikap Keuangan, Pengetahuan Keuangan, dan Self Esteem pada Mahasiswa Pendidikan Ekonomi UNS - Elvina Dhamayanti; Harini Harini (Departement of Mathematics Education, 2024)
This study aims to examine the effect of parental financial teaching on financial behavior which is mediated by financial attitudes, financial knowledge and self-esteem. The conceptual model of parental financial socialization and experiential learning theory (ELT) were used as theoretical frameworks and structured questionnaires were used to collect data. A total of 229 active students of UNS Economics Education were the samples in this research. The sampling technique used is probability sampling with the proportionate random sampling method. Data analysis uses the structural equation modeling (SEM-PLS) method. The research results show that: (1) parental financial teaching has a positive and significant effect on students' financial behavior. (2) parental financial teaching has a positive and significant effect on students' financial attitudes. (3) student financial attitudes have a positive effect on student financial behavior. (4) parents' financial teaching has a positive and significant effect on students' self-esteem. (5) parental financial teaching has a positive and significant effect on students' financial knowledge. (6) self-esteem has a positive and significant effect on students' financial attitudes. (7) financial knowledge has no significant effect on students' financial attitudes. (8) self-esteem has a positive and significant effect on student financial behavior. (9) financial knowledge has a positive but not significant effect on student financial behavior.